Sistema informático web de gestión de incidencias usando el framework AngularJS y Node.js para la empresa Redteam Software LLC - Tacilla Ludeña, Julio Luis (2016)
This thesis is developed under the problematic identified in the process of incident management of the company RedTeam Software LLC, in which was identified how main problem a delay or inattention incidents and the need of increment the customer satisfaction with reported incidents solution. The present work has as purpose offer a solution with a development of information system web using the frameworks AngularJS and NodeJs to management incidents for the Company Redteam Software LLC, for this the current situation of the incident management process was analyzed for the purpose of identify the main requirements which then will be the base for the development of this work For Development was used the methodology ICONIX, this permitted have a development agile and fast showing the analysis, design and implementation of the informatics system web.